Community structure and population genetics of Eastern Mediterranean polychaetes - Chatzigeorgiou, Giorgos; Sarropoulou, Elena; Vasileiadou, Katerina; Brown, Christina; Faulwetter, Sarah; Kotoulas, Giorgos; Arvanitidis, Christos D. (Frontiers in Marine Science, 2014)
Species and genetic diversity are often found to co-vary since they are influenced by external factors in similar ways. In this paper, we analyse the genetic differences of the abundant polychaete Hermodice carunculata (Pallas, 1776) during two successive years at two locations in northern Crete (Aegean Sea) and compare them to other populations in the Mediterranean Sea and the Atlantic Ocean. The genetic analysis is combined with an analysis of ecological divergence of the total polychaete community structure (beta diversity) at these locations. The phylogenetic analysis of all included H. carunculata populations revealed two main clades, one exclusively found in the Mediterranean and a second occurring in both the Mediterranean and the Atlantic. Genetic diversity indices reveal unexpectedly high differences between the two Cretan populations, despite the absence of apparent oceanographic barriers. A similarly high divergence, represented by a high beta diversity index, was observed between the polychaete communities at the two locations. This comparatively high divergence of the genetic structure of a dominant species and the total polychaete community might be explained by the strong influence of local environmental factors as well as inter-specific interactions between the dominance of a single species and the members of the community.